Gamification elements and online resources for teaching english lexics to future engineers at technical university - Nina S. Shvaikina; Kseniya S. Oparina; Elena I. Kolosova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to gamification as one of the leading trends in all branches of human activity, including education. A modern young professional should have a formed foreign language communicative competence to perform professional duties in the most effective way. In addition, knowledge of a foreign language contributes to the harmonious development of the individual and provides a basis for further achievements. The aim of this paper is to define the concept of gamification in educational discourse, to identify its key characteristics, as well as the differences from the concept of game. In the practical part of the paper, the authors made an attempt to determine the effectiveness of gamification and online sources for teaching English vocabulary to engineering students. In addition, a list of specific online resources that can be used in the classroom is given. This research was carried out using theoretical and practical methods. The theoretical methods are the analysis of the Federal State Educational Standard of Higher Education and other regulatory documents, regulating the learning process at the university, as well as reviewing and systematizing the theoretical and practical works of researchers in this area. The results of the practical part of the research were obtained through pedagogical observation, questionnaires, testing and experiment, as well as through a frontal conversation and an individual interview. The research results can be applied in teaching English to bachelor students of all technical areas of training, as part of a refreshment course for undergraduates of non-linguistic specialties. In addition, it should be noted that the use of gamification is possible both in classroom lessons and in the independent work of students.